Decreased skin colonization with Malassezia spp. and increased skin colonization with Candida spp. in patients with severe atopic dermatitis - Storz, Lukas; Schmid, Bettina; Bosshard, Philipp Peter; Schmid-Grendelmeier, Peter; Brüggen, Marie-Charlotte; Lang, Claudia (Frontiers in Medicine, 2024)
Background Atopic dermatitis (AD) is a chronic relapsing inflammatory skin disease in which patients are sensitized towards a plethora of allergens. The hosts fungal microbiota, the mycobiota, that is believed to be altered in patients suffering from AD acts as such an allergen. The correlation context of specific sensitization, changes in mycobiota and its impact on disease severity however remains poorly understood. Objectives We aim to enhance the understanding of the specific sensitization towards the mycobiota in AD patients in relation to their fungal skin colonization. Methods Sensitization pattern towards the Malassezia spp. and Candida albicans of 16 AD patients and 14 healthy controls (HC) were analyzed with the newly developed multiplex-assay ALEX2® and the established singleplex-assay ImmunoCAP®. We compared these findings with the fungal skin colonization analyzed by DNA sequencing of the internal transcribed spacer region 1 (ITS1). Results Sensitization in general and towards Malassezia spp. and C. albicans is increased in AD patients compared to HC with a quantitative difference in severe AD when compared to mild to moderate AD. Further we saw an association between sensitization towards and skin colonization with Candida spp. yet a negative correlation between sensitization towards and skin colonization with Malassezia spp. Conclusion We conclude that AD in general and severe AD in particular is associated with increased sensitization towards the hosts own mycobiota. There is positive correlation in Candida spp. skin colonization and negative in Malassezia spp. skin colonization when compared to AD, AD severity as well as to specific sensitization patterns.